2010
DOI: 10.1515/jpem.2010.141
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences in Fat Distribution in Non-Obese Japanese Children

Abstract: Objective: To assess fat distribution in non-obese Japanese children and adolescents. Design: 130 non-obese Japanese children (73 boys and 57 girls) from Kikugawa, Hamamatsu were included. The visceral fat area (VFA) and subcutaneous fat area (SFA) were measured by computed tomography (CT) and calculated (in cm 2 ). Subjects were divided into three groups based on age: group A (6-10 years), group B (11-15 years), and group C (16-20 years). Results: Girls had more subcutaneous fat than boys in groups B and C (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…Regarding SC fat, some authors have shown that differences between sexes already occur in childhood from the first year of life on (12,(22)(23)(24)(25), which could also be demonstrated by our findings. These observations differ from studies that provided no evidence of gender-specific differences under the age of ten (22,25). Regarding PP fat, sex differences in visceral fat seem to be closely linked to age-and puberty-related changes in fat distribution (8,22).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding SC fat, some authors have shown that differences between sexes already occur in childhood from the first year of life on (12,(22)(23)(24)(25), which could also be demonstrated by our findings. These observations differ from studies that provided no evidence of gender-specific differences under the age of ten (22,25). Regarding PP fat, sex differences in visceral fat seem to be closely linked to age-and puberty-related changes in fat distribution (8,22).…”
Section: Discussionsupporting
confidence: 86%
“…Regarding PP fat, sex differences in visceral fat seem to be closely linked to age-and puberty-related changes in fat distribution (8,22). However, the question remains open when such differences in fat patterning first emerge because data in early childhood show conflicting results (9,12,15,22,23,25,26). Further follow-up investigations in children, especially for internal fat, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Satake, et al reported similar findings in 130 non-obese Japanese children. [34] They divided the children in 3 age groups ranging from 6 through 20 years of age. They noticed more VAT in boys only in the highest age group of 16–20 year olds.…”
Section: Discussionmentioning
confidence: 99%
“…28 Additionally, girls had more SAT in a CT study of 11–20-year-old Japanese adolescents, 49 and girls had more abdominal SAT in a sample of British 12–14-year-olds. 8 Whole-body SAT was also higher in pubertal adolescent girls in an MRI study of 5–17-year-olds in the US.…”
Section: Influence Of Sexmentioning
confidence: 99%
“…48 Although 6–16-year-olds in Japan had no sex differences in VAT, older adolescent boys aged 16–20 had more VAT than their female counterparts. 49 Importantly, obesity increases android fat distribution in both sexes, thereby decreasing sex differences in body shape. 38 …”
Section: Influence Of Sexmentioning
confidence: 99%